2001
DOI: 10.1023/a:1010521108884
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although thyroid hormones induce a well known decrease in muscle oxidative capacity, nothing is known concerning their effects on mitochondrial function and regulation in situ. Similarly, the influence of regeneration process is not completely understood. We investigated the effects of hypothyroidism on mitochondrial function in fast gastrocnemius (GS) and slow soleus (SOL) muscles either intact or having undergone a cycle of degeneration/regeneration (Rg SOL) following a local injection of myotoxin. Thyroid h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that permeabilized cells and muscle fibers are suitable for in situ affinity analysis of the main substrate of phosphorylation, ADP. This is done by measuring its apparent Km value as a sensitive parameter of the organization and functional state of mitochondria and mitochondrial membranes (Veksler et al, 1995; Zoll et al, 2001, 2002; Burelle and Hochachka, 2002). Classical studies of ADP kinetics have shown that preparations of isolated mitochondria exhibit a very high affinity for ADP (low apparent Km value for ADP in the range 10–25 μM).…”
Section: Studies Of In Situ Mitochondria: Properties Of Mitochondria mentioning
confidence: 99%
“…Previous studies have shown that permeabilized cells and muscle fibers are suitable for in situ affinity analysis of the main substrate of phosphorylation, ADP. This is done by measuring its apparent Km value as a sensitive parameter of the organization and functional state of mitochondria and mitochondrial membranes (Veksler et al, 1995; Zoll et al, 2001, 2002; Burelle and Hochachka, 2002). Classical studies of ADP kinetics have shown that preparations of isolated mitochondria exhibit a very high affinity for ADP (low apparent Km value for ADP in the range 10–25 μM).…”
Section: Studies Of In Situ Mitochondria: Properties Of Mitochondria mentioning
confidence: 99%